Pengenalan Pembelajaran Inovatif Berbasis AI Menggunakan Pictoblox untuk Meningkatkan Literasi Digital dan 4C Skills Siswa SMKN 2 Pekanbaru - Susanti; Dewi Sari Wahyuni; T. Sy. Eiva Fatdha; Triyani Arita Fitri; Muhammad Jamaris (TENANG : Teknologi, Edukasi, dan Pengabdian Multidisiplin Nusantara Gemilang, 2025)
The development of the Fourth Industrial Revolution and the Society 5.0 era requires vocational schools to equip students with digital literacy, computational thinking skills, and 4C abilities (critical thinking, creativity, communication, and collaboration). Nevertheless, many teachers and students in vocational schools are not yet familiar with artificial intelligence (AI) technology and innovative learning media. This community-engagement article describes PictoBlox training, a visual programming software with AI extensions, for 34 students from the Software Engineering program of SMKN 2 Pekanbaru, aimed at improving digital literacy, computational thinking skills, and learning motivation. The training was organized as project-based learning in two sessions: introducing AI concepts, familiarizing students with the PictoBlox interface, practising simple projects (educational games and a facial recognition system), evaluating progress through pre-test and post-test, and reflection. Results show that the average score increased from 48 (pre-test) to 80 (post-test); 80 % of participants completed the projects, and their 4C skills improved. These findings are supported by research showing that PictoBlox facilitates concretization, visualization, and interactive content creation and enhances computational thinking skills. Moreover, integrating project-based learning with ICT has been proven to improve students’ collaboration, creativity, and communication, although it requires teacher training and support, as well as resources. This activity provides a model for implementing AI in vocational schools and recommends further mentoring and the integration of PictoBlox into the curriculum.